2019
DOI: 10.1007/s00595-019-01877-8
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative predictors of postoperative complications after gastric cancer resection

Abstract: Risk management is becoming an increasingly important healthcare issue. Gastrectomy with lymphadenectomy is still the mainstay of treatment for localized gastric cancer, but it is sometimes associated with postoperative complications that compromise the patient's quality of life, tolerability of adjuvant treatment, and prognosis. Parameters based exclusively on preoperative factors can identify patients most at risk of postoperative complications, whereby surgeons can provide the patient with precise informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 78 publications
1
41
1
8
Order By: Relevance
“…Based on these results, a lower preoperative hemoglobin level may compromise general tissue oxygenation and hence result in the occurrence of complications. Conversely, preoperative BMI, NLR, or serum albumin levels were reported as a significant risk factor for overall complications after gastrectomy in all generations (23). These preoperative factors did not affect elderly patient morbidity in this study.…”
Section: Discussioncontrasting
confidence: 47%
“…Based on these results, a lower preoperative hemoglobin level may compromise general tissue oxygenation and hence result in the occurrence of complications. Conversely, preoperative BMI, NLR, or serum albumin levels were reported as a significant risk factor for overall complications after gastrectomy in all generations (23). These preoperative factors did not affect elderly patient morbidity in this study.…”
Section: Discussioncontrasting
confidence: 47%
“…Symptomatic patients with obstruction, perforation, and bleeding should not be delayed. We must consider that gastrectomy is a relatively morbid operation with reported complication rates ranging from 13–46% [ 29 ]. This could further make these patients immunocompromised as well as put them in an environment with greater viral transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, other studies have reported that the occurrence of postoperative surgical complications influences the recurrence pattern and patient survival in various malignancies (25,26). Therefore, patients with a high CAR tend to more frequently develop postoperative surgical complications compared to those with a low CAR, and the occurrence of surgical complications might then lead to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%